Legal Regulation of the Migration Processes in the Russian Federation - Burinova, Lidyia Dadunovna; Burinov, Artur Mikhailovich; Dorzhi-Goryaeva, Elza Vladimirovna; Oldeeva, Delya Antonovna (Journal of History Culture and Art Research, 2018)
The article is devoted to the analysis of legal regulation of the migration processes in the constituent entities of the Russian Federation on the example of the Republic of Kalmykia. Activities of the migration services and other subjects of legal relations in the process of implementation of legal provisions in this sphere have been studied in the paper. Internal migration has also been analyzed. The research has shown that the state regulation of the migration processes is one of the directions of the state policy aimed at their organization and management by the state administrative authorities with the use of the administrative, legal and socio-economic forms and methods in order to achieve the interests of the state in the sphere of social, demographic and economic development of the society in compliance with the principles of international and Russian laws. Bringing Russian legislation in the field of migration to democratic international standards implies a balance of the federal legislation and legislation of the constituent entities of the Russian Federation, development and adoption of the regulatory legal acts reflecting contemporary status of migration processes in reforming Russia, and taking into account external and internal diversity of migrants. The study has indicated that the migration sphere in the Russian Federation is regulated by several hundred of international and national regulatory legal acts of different juridical force, which solve different aspects of the problem but can not regulate the existing situation in its complexity in the framework of interests of the participants of the state migration policy. The need for codification of the Russian migration legislation is argued in the article.